THE APPLICATION OF PYROLYSIS GAS AS A FUEL FOR GAS TURBINE ENGINES FOR ELECTRICITY GENERATION - Obodovskyi, Ivan; Morozov, Viacheslav (Proceedings of National Aviation University (archive), 2021)
Purpose: The purpose of this article is to show the opportunities of application of the pyrolysis gas as a fuel for gas turbine power plants based on decommissioned gas turbine engines, including those from aircraft – either turboprop or turboshaft, or both, and also those used on ground vehicles such as tanks and marine engines as well. Methods: The article describes the technology of pyrolysis of different materials for obtaining pyrolysis gas and its further application as a fuel for internal combustion engines was developed in the end of XIX century and was successfully applied for automobile, marine and railway locomotive piston engines till the mid ХХ century when large oil reservoirs were discovered all around the World. Results: the current research not only proves that there exists an economic benefit of application of pyrolysis technology even at nowadays, but also an ecological one, allowing getting rid of garbage Discussion: The proposed examples of successful pyrolysis technology application can be a good basis for further research of transferring modern engines to the pyrolysis gas fuels.